Penggunaan Aplikasi Desain Gambar dan Video Bajakan untuk Dakwah dalam Perspektif Hukum Islam - Mukran H. Usman; Muhammad Ikhsan; Fitra Abadi (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2024)
This research aims to find out and understand legal concepts using pirated image design and video design applications for da'wah from an Islamic legal perspective. The method used in this research is a qualitative method with a normative approach as well as a philosophical and historical approach. The data sources come from primary data obtained from the Al-Qur'an and Hadith, secondary data in the form of written information from literature. Data collection uses the methods of reading, studying, reviewing, analyzing and the final stage of drawing conclusions. The research results found are as follows. First, based on the history of graphic design, in this case image and video design is now a necessity in almost all corners of life so both are important things today. Second, the legal origin of all acts of piracy is something that is not permitted because it is an act of taking someone else's rights without permission from the owner. This is also a big sin because the perpetrator is cursed by Allah SWT. Even though it is in the name of da'wah which is indeed an obligation, there are two conditions that make piracy of image and video design applications something that is permissible in emergency conditions for da'wah, namely paying attention to the signs and limits in application piracy behavior.